(untitled) (Global Journal of Science Frontier Research, 2016)
Indigenous chickens in Ethiopia are found in huge numbers distributed across different agro ecological zones under a traditional family-based scavenging management system. This indicates that, they are highly important farm animals kept as a source of animal protein and income to most of the rural populations. Religions and cultural considerations are also amongst the reasons for keeping chickens by resource poor farmers in Africa. Similarly, households in Ethiopia keep birds for household consumption, sale and reproduction purposes including other social and cultural roles. Ethiopia, with its wide variations in agro-climatic conditions, possesses one of the largest and the most diverse plant and animal genetic resources in the world. Therefore, this study was conducted from September 2013 to May 2014 in nine selected kebeles and South bench Woreda’s located in Bench Maji Zone of South western of Ethiopia with the objective to describe indigenous chicken husbandry practices and production system.